«ICH STEIG’ AN’S LAND, NICHT OHNE FURCHT UND ZAGEN», OVVERO L’ARRIVO A VENEZIA DI AUGUST VON PLATEN E L’INIZIO DEI SONETTI VENEZIANI - Serena Spazzarini (Sinestesieonline, 2018)
In Italy, and in particular in Venice, August von Platen Hallermünde spent long periods and wrote a large number of works. In 1825 he published the Sonette aus Venedig (Sonetti Veneziani) in Erlangen. The first part of the paper provides a general introduction to the relations between Platen and Italy and summarizes the «complicated» genesis of this poetical cycle. The second part focuses in more details on a linguistic and rhetorical analysis of the sequence’s first sonnet. Finally, the third part proposes a reflection on possible similarities between the narrative structure of Platen’s sonnets and Thomas Mann’s Death in Venice.